A syndrome of microcephaly, short stature, polysyndactyly, and dental anomalies caused by a homozygous KATNB1 mutation. Issue 3 (6th December 2015) - Yigit, Gökhan; Wieczorek, Dagmar; Bögershausen, Nina; Beleggia, Filippo; Möller‐Hartmann, Claudia; Altmüller, Janine; Thiele, Holger; Nürnberg, Peter; Wollnik, Bernd
Abstract : Using whole‐exome sequencing, we identified a homozygous acceptor splice‐site mutation in intron 6 of the KATNB1 gene in a patient from a consanguineous Turkish family who presented with congenital microcephaly, lissencephaly, short stature, polysyndactyly, and dental abnormalities. cDNA analysis revealed complete loss of the natural acceptor splice‐site resulting either in the usage of an alternative, exonic acceptor splice‐site inducing a frame‐shift and premature protein truncation or, to a minor extent, in complete skipping of exon 7. Both effects most likely lead to complete loss of KATNB1 function. Homozygous and compound heterozygous mutations in KATNB1 have very recently been described as a cause of microcephaly with brain malformations and seizures. We extend the KATNB1 associated phenotype by describing a syndrome characterized by primordial dwarfism, lissencephaly, polysyndactyly, and dental anomalies, which is caused by a homozygous truncating KATNB1 mutation. © 2015 Wiley Periodicals, Inc.